2023
DOI: 10.1126/sciimmunol.adc9584
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 acts as both a sensor and a sink for CCL19 to coordinate collective leukocyte migration

Jonna Alanko,
Mehmet Can Uçar,
Nikola Canigova
et al.

Abstract: Immune responses rely on the rapid and coordinated migration of leukocytes. Whereas it is well established that single-cell migration is often guided by gradients of chemokines and other chemoattractants, it remains poorly understood how these gradients are generated, maintained, and modulated. By combining experimental data with theory on leukocyte chemotaxis guided by the G protein–coupled receptor (GPCR) CCR7, we demonstrate that in addition to its role as the sensory receptor that steers migration, CCR7 al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Subsequent studies indicated the interaction between the chemokine, CCL19, and its ligand CCR7, which is typical of T cell activation in lymphoid structures as a key event for the recruitment of these cells also in psoriatic skin [72]. In the dermis of psoriatic plaques, the presence of a lymphoid aggregates has been reported by Mitsui and colleagues, evidencing also the expression of CCL19 and CCR7 [73].…”
Section: T Cells In Psoriasis Pathogenesismentioning
confidence: 86%
“…Subsequent studies indicated the interaction between the chemokine, CCL19, and its ligand CCR7, which is typical of T cell activation in lymphoid structures as a key event for the recruitment of these cells also in psoriatic skin [72]. In the dermis of psoriatic plaques, the presence of a lymphoid aggregates has been reported by Mitsui and colleagues, evidencing also the expression of CCL19 and CCR7 [73].…”
Section: T Cells In Psoriasis Pathogenesismentioning
confidence: 86%
“…Focusing on the cycle of the anti-tumor immune response ( Figure 3 ), it begins with the release and capture of neoantigens, generated during oncogenesis, by antigen-presenting cells (APCs), such as dendritic cells (DCs). These cells process the antigens and undergo a maturation process, which involves an increase in the expression of various molecules, such as the chemokine receptor CCR7 ( 24 26 )and the migration of DCs to the lymph nodes where they can interact with T cells ( 24 ), driving complex collective migration patterns, allowing DCs to create or enhance chemotactic gradients ( 24 ). For an anti-tumor T response to be generated, this process needs to be accompanied by signals that prevent peripheral tolerance to tumor antigens, such as high expression of major histocompatibility complex (MHC) molecules and co-stimulatory molecules (such as CD80, IL1, IFN-α) ( 27 ).…”
Section: Relevant Sections and Discussionmentioning
confidence: 99%
“…Through this internalization process, DCs generate a self-generated chemokine gradient. However, when chemokine gradients are low, DCs are difficult to perceive, whereas high gradients lead to receptor saturation, hindering cells from sensing spatial differences [ 71 73 ]. Stable gradients of CCL19 are crucial for stabilizing directionality because disruption of these gradients leads to impaired cytoskeletal polarization and persistent chemotaxis.…”
Section: Migration Of Dcsmentioning
confidence: 99%